PENGARUH KONSENTRASI NaCHO3 DAN LAMA PEREBUSAN TERHADAP SIFAT FISIK, KANDUNGAN KALSIUM OKSALAT DAN NILAI TAMBAH TEPUNG SUWEG (Amorphophallus campanulatus) - Ulfah Anis; Hidayat Koto; Syafnil Syafnil (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Negeri Tanah Laut, 2022)
Suweg tubers can be found in the Empat Lawang area, South Sumatra. The local community has not used the suweg tubers to be processed into food products because people only know them as wild plants that can cause itching. Suweg tubers also contain nutrients such as protein, carbohydrates, fats, minerals, vitamins, and a low glycemic index. The itching effect on the skin is due to calcium oxalate in the suweg tuber. Therefore, it is necessary to reduce the calcium oxalate content in suweg tuber flour. This study aims to determine the effect of boiling time and the addition of NaCHO3 with various concentrations on the water content, color, calcium oxalate content, and added value of the resulting suweg flour. This study used a completely randomized design with two factors: the concentration of NaCHO3 (6%, 8%, and 10%) and boiling time (10 minutes, 20 minutes, and 30 minutes). The results showed that the concentration of added NaCHO3 affected the calcium oxalate content of suweg flour. Boiling time affected the water content and calcium oxalate content of suweg flour. The greater the concentration of NaCHO3 added and the longer the boiling time affected the color of the suweg flour becomes medium brown. Suweg flour has an added value of Rp. 10.070,- /kg.